HEPATITIS B AND HEPATITIS C SEROPOSITIVE SURGICAL CASES AND ITS IMPACT ON PERIOPERATIVE BLOOD TRANSFUSION: Hepatitis B and C Seropositive Surgical Cases - Ikram, Mobeen; Mahboob, Saira; Yusuf, Rizwan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the frequency of Hepatitis B and Hepatitis C on our surgical patients and its impact on operation theater delay, change of anesthesia plan and requirement of perioperative blood and blood products transfusion.Study Design: Cross sectional, analytical study.Place and Duration of Study: Department of Anesthesiology, Combined Military Hospital, Okara, from Apr to Sep 2019.Methodology: After the approval of the hospital ethical review committee, 154 patients with either Hepatitis B or Hepatitis C undergoing various surgeries were included in our study. Data was analyzed using SPSS-20.Results: The overall frequency of chronic liver disease was 154 (4.71%). A total of 23 (0.70%) were found to be seropositive as viral Hepatitis B and 127 (3.88%) as Hepatitis C; whereas 4 (0.12%) patients were diagnosed to have both virus serology positive. There was mean delay of 26.2 ± 8.29 minutes in 78 (52%) patients. The anesthetist had to change the plan of anesthesia for only 1 (0.7%) patient. There was also no difference in frequency of change of anesthesia plan (p=0.35); delay in surgery (p=0.16) and blood transfusion between the patients with Hepatitis B or Hepatitis C infection (p=0.72).Conclusion: The frequency of Hepatitis B and Hepatitis C was lower (4.71%) in our surgical patients with no effect of Hepatitis B and Hepatitis C on blood loss, peri-operative transfusion, delay in surgery or change in anesthesia plan.